STAT3 drives the malignant progression of low-grade gliomas through modulating the expression of STAT1, FOXO1, and MYC - Li, Yan; Jiang, Fanjing; Zhu, Suhua; Jia, Hongwei; Li, Changwei (Frontiers in Molecular Biosciences, 2024)
Low-grade glioma (LGG) is a prevalent and lethal primary brain malignancy, with most patients succumbing to recurrence and progression. The signal transducer and activator of transcription (STAT) family has long been implicated in tumor initiation and progression.However, a comprehensive evaluation of the expression status and overall function of STAT genes in LGG remains largely unreported. In this study, we investigated the association between the expression of STAT family genes and the progression of LGG. Through a comprehensive analysis that combined bioinformatics screening and validation assays, we determined that STAT1, STAT3, and STAT5A were upregulated and contributed to the malignant progression of LGG. Notably, our findings suggest that STAT3 is a critical prognostic marker that regulates the progression of LGG. STAT3 emerged as the most significant prognostic indicator governing the advancement of LGG. Additionally, our inquiry into the STAT3-binding proteins and differentially expressed-correlated genes (DEGs) revealed that STAT3 played a pivotal role in the progression of LGG by stimulating the expression of STAT1, FOXO1, and MYC. In summary, our recent study conducted a thorough analysis of the STAT family genes and revealed that directing therapeutic interventions towards STAT3 holds potential as a viable strategy for treating patients with LGG.